MEMBANGUN KREATIVITAS SISWA UNTUK MERSEPONS KOMPETENSI DIGITAL MELALUI KEPEMIMPINAN INSTRUKSIONAL DI MTS NW SUELA - Azwar, Chairul Azwar; Dini, Hardini Rahmatin Utami; Yudin, Yudin Citriadin (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
Creativity can be defined as a individual’s ability to create new ideas and produce products through experience, insight and knowledge. The aim of the research to build student creativity in responding to this digital competition is to find out the extent to which students are able to develop themselves in facing the 5.0 era of integrating and applying technology into life in the form of creativity in a smarter way in the competitive digital world. Students are expected to be able to increase creativity through instructional leadership at school, of course with the principal's strategy in applying his leadership in increasing student creativity by sharpening digital skills, adopting an innovative mindset, collaborating and building networks, utilizing digital opportunities and seeking inspiration from creative sources. This is a very important strategy in education, learning and self-development as an integral part of the learning process. In this research, researchers used descriptive qualitative methods. This research is expected to be able to provide the expected results in the form of students' ability to apply technology in the current digital era and the emergence of student creativity through technology.